2000
DOI: 10.1021/ja002112w
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Calix[4]pyrrole and Dipyrrolylquinoxaline:  Neutral Anion Receptors with Augmented Affinities and Enhanced Selectivities

Abstract: The use of the 3,4-difluoro-1H-pyrrole as a building block for the preparation of octamethyloctafluorocalix[4]pyrrole and 2,3-di(3‘,4‘-difluoropyrrol-2‘yl)quinoxaline is described. These latter two entities act as neutral anion receptors and were found to bind anions such as fluoride, chloride, or dihydrogen phosphate with an enhanced affinity compared to their non-fluorinated congeners as judged from 1H NMR, 19F NMR, and fluorescence emission spectroscopic analyses. The increase in affinity was especially hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
164
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(177 citation statements)
references
References 11 publications
12
164
0
1
Order By: Relevance
“…[134,135] Sessler and co-workers also discovered that calix [4]pyrroles act as receptors for anions as well as for neutral substrates, a finding that has been extended to other calixpyrroles. [136][137][138] Not surprisingly in view of the discussion in Sections 5 and 6 on the synthesis of b-perfluorinated porphyrins, corroles, and expanded porphyrins from 3,4-difluoropyrrole and an aldeyhyde, Sessler and co-workers found that 3,4-difluoropyrrole undergoes a condensation reaction with acetone to yield octafluorocalix [4]pyrrole (Scheme 18) selectively; [139] carefully optimized conditions also permitted the isolation of decafluorocalix [5]pyrrole and hexadecafluorocalix [8]pyrrole. [140] Octafluorocalix [4]pyrrole was found to exhibit a dramatically enhanced affinity toward anionic ligands relative to nonfluorinated calixpyrroles.…”
Section: A Digression On Calixpyrrolesmentioning
confidence: 99%
“…[134,135] Sessler and co-workers also discovered that calix [4]pyrroles act as receptors for anions as well as for neutral substrates, a finding that has been extended to other calixpyrroles. [136][137][138] Not surprisingly in view of the discussion in Sections 5 and 6 on the synthesis of b-perfluorinated porphyrins, corroles, and expanded porphyrins from 3,4-difluoropyrrole and an aldeyhyde, Sessler and co-workers found that 3,4-difluoropyrrole undergoes a condensation reaction with acetone to yield octafluorocalix [4]pyrrole (Scheme 18) selectively; [139] carefully optimized conditions also permitted the isolation of decafluorocalix [5]pyrrole and hexadecafluorocalix [8]pyrrole. [140] Octafluorocalix [4]pyrrole was found to exhibit a dramatically enhanced affinity toward anionic ligands relative to nonfluorinated calixpyrroles.…”
Section: A Digression On Calixpyrrolesmentioning
confidence: 99%
“…11 Such as, Atwood et al 12 found that the conformation of 25,26,27,28-tetramethoxy-p-tert-butylcalix [4]arene is modified either to 1,2-alternate or to 1,3-alternate through complexation with different aluminum alkyl compounds. Marquez and Sessler et al 13 revealed the presence of four different macrocyclic conformations in the solid state by using different substrates. Recently, we reported that an interlocked 2-D supramolecular architecture was constructed through the synergistic intermolecular interactions of 25,27-bis(4-nitrobenzoate)-26,28-dihydroxy-calix [4]arene in the crystal, which were highly stabilized by the regular π-π and offset stacking, edge-to-face, and/or dipole-dipole interactions.…”
Section: Introductionmentioning
confidence: 99%
“…21 The β-functionalized calixpyrroles are also attractive since the β-substituents can modulate the affinity of the calixpyrrole. 22 The substituents can act as a reporter group 23 or provide a synthetic versatilities for further functionalization including immobilisation of the macrocycle. 24 Octa-bromo-meso-octamethylcalix[4]-pyrrole 2 is one of the first examples studied in terms of the effect of the substitutents on anion binding.…”
mentioning
confidence: 99%